The debt conundrum and monetary policy implications on exchange rate in South Africa - Molele, S. B.; Mashishi, N. P. (FMLIC - Conference Proceedings, 2024)
The relentless dance of South Africa's exchange rate performance and rising external debt calls for an indepth examination of their intertwined dynamics, considering monetary policy implications. The country's significant external debt burden increased the risk of currency depreciation, inflationary pressures and economic uncertainty, posing major challenges for market participants, and hindering foreign investment. This study investigated the relationship between external debt, domestic and global interest rates, and inflation on the exchange rate in the context of South Africa for the period 1992 to 2023. The study employed a quantitative methodology utilizing the Autoregressive Distributed Lag (ARDL) model to account for the relationships. Additionally, short-run causality and dynamic shock analysis were utilized. The results indicated that high external debt levels significantly depreciated the exchange rate, a phenomenon intensified by rising domestic interest rates and inflation, while fluctuations in the global interest rates add further to the movement of the Rand. The external debt, inflation and domestic interest rates had a positive and significant effect on the exchange rate in the long run. Moreover, external debt and global interest rate had a positive and significant short run effects on exchange rate. Additionally, when all variables were combined, a short-run causality existed. Furthermore, only external debt and global interest rates had a short-run causality effect on exchange rates. Moreover, shocks in external debt and inflation led to depreciation, and the domestic and global interest rate had a positive shock effect on exchange rate. The findings highlighted the critical need for effective external debt management and sound monetary policies to maintain exchange rate stability in South Africa. The Rand fluctuations have a sound impact on international financial markets, affects investor sentiment, capital flows, and currency valuations in other countries. As South Africa serves as a case study for many emerging African economies.
Keywords: Exchange rate; External debt; Inflation rate; Interest rates